PEMBUATAN KERTAS INDIKATOR ALAMI SEBAGAI ALAT PRAKTIKUM PENENTUAN SIFAT ASAM DAN BASA SUATU LARUTAN - Safitri Safitri; Husna Amalya Melati; Lukman Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to synthesis the natural indicator paper, determine the range of pH and its feasibility. Synthesis natural indicator paper from turmeric extract (Curcuma domestica), hibiscus flowers extract (Hibiscus rosasinensis), adam hawa extract (Rhoeo discolor), asoka flowers extract (Saraca indica), determine the range of pH and its feasibility. The extract synthesis in paper form and be used as practical tool to replace litmus paper in determining acid-base characteristics of solution. This research was using  qualitative method. This research was conducted in two stages, which were the synthesis of indicator paper and determine the range of pH and feasibility. Data collection techniques were carried out by  using observation sheets to testing acid-base indicator paper from plant extracts and questionnaires for testing the feasibility of indicator paper by several teachers of the Junior High School in Tebas. The results showed that the range of pH and its colour change of hibiscus flowers, adam hawa, asoka flowers and turmeric were respectively, 4-10 (red-green), 6-8 (red-green), 4-10 (red-green), 9-10 (yellow-brownish red). The results of the feasibility of indicator paper obtained at 97.04%. It can be concluded that acid-base indicator paper from natural resource can be used as a science learning practice tool in the Junior High School in Tebas, West Kalimantan Province. Keywords: Feasibility, Natural Indicator, Range pH